An inexpensive robotic gantry to screen and control soil moisture for plant experiments. (April 2021) - Takara, Grant; Zachary Trimble, A.; Arata, Reika; Brown, Shane; Jaime Gonzalez, Hector; Mora, Camilo
Graphical abstract: Abstract: Controlling water content in soil is a recurrent and labor intensive operation on almost any experiment about plant physiology. Here we describe a robotic gantry to measure and control soil moisture in pots that is modular, inexpensive, easy to build, accurate, precise, and reliable. Machines can be stacked into industrial shelves, coupled with other control systems to conduct multifactorial experiments, and adjusted to accommodate numerous pots of any size allowing for experiments with limitless specimen capacity in terms of height and specimen count. The system can be assembled in up to seven hours using off the shelf components and simple tools at a total cost of 1, 276, in 2019 prices. A screening cycle can be performed as fast as every six minutes reducing variations in water content due to evaporation and thus creating precise control of soil moisture. As a validation of the long-term cyclic reliability of the system, the machine was run non-stop for 4480 loops; the equivalent to running an experiment for six months controlling water content every hour. By facilitating high throughput monitoring of soil moisture in pots, reliably and at low cost, this machine can facilitate the development of large-scale experiments on plant physiology.